Peritoneal Ultrafiltration for Heart Failure: Lessons from a Randomized Controlled Trial. Issue 5 (September 2019) - Dukka, Hari; Kalra, Philip A.; Wilkie, Martin; Bhandari, Sunil; Davies, Simon J.; Barratt, Jonathan; Squire, Iain; Odudu, Aghogho; Selby, Nicholas M.; McIntyre, Christopher; Robertson, Fiona; Taal, Maarten W.
Peritoneal ultrafiltration (PuF) has been employed for severe heart failure (HF), but evidence for its benefit is lacking. The Peritoneal Dialysis for Heart Failure (PDHF) study was a multicenter prospective randomized controlled trial which aimed to investigate this issue. The trial stopped early due to inadequate recruitment. We describe methods, trial activity, and lessons learned. The trial aimed to recruit 130 participants with severe diuretic-resistant HF (New York Heart Association [NYHA] 3/4) and chronic kidney disease (CKD) stage 3/4 on optimal medical treatment for ≥ 4 weeks from 6 UK centers. Participants were randomized to either continuation of conventional HF treatment or to additionally receiving PuF (1 overnight exchange using Icodextrin dialysate). Primary outcome was change in 6-minute walk test (6MWT) between baseline and 28 weeks (end of trial). Secondary outcomes were changes in patient reported quality of life as assessed by the Kansas City Cardiomyopathy Questionnaire, short form 36 (SF 36) health survey results, hospitalization, and mortality. Over a 2-year period, 290 patients were screened from which only 20 met inclusion criteria and 10 were recruited. Reasons for ineligibility were fluctuating estimated glomerular filtration rate (eGFR), suboptimal HF treatment, frailty, and patients being too unwell for randomization. Barriers to recruitment included patient frailty, with some participants considered only when they were at end of life, unwillingness to engage in an invasive therapy, and suboptimal coordination between cardiology and renal services. This is a challenging patient group in which to perform research, and lessons learned from the peritoneal dialysis (PD)-HF trial will be helpful in the planning of future studies in this area.